Reduction pattern of relative length of chromosomes- A new approach for taxonomic comparison in cattle - Sarkhel, B C; Katpatal, B G (The Indian Journal of Animal Sciences, 2012)
A new approach for studying the taxonomic relationship between 3 pure breeds and their 2-breed and 3-breed crossbreeds was undertaken. The adjusted values of relative length of chrosomes of 7 genetic groups were graphically represented and slope of reduction pattern was compared in 2 separate graphs. One for 3 pure breeds and other for 4 crossbred genetic groups. The slope of reduction from autosome No. 8 to 12 was most in Holstein-Friesian and least in Jersey. The pattern of slope indicated that Jersey (Ros taurus) breed was more close to Gir (Bos indicus ) breed than another Bos taurus (Holstein-Friesian) breed.